Pengembangan Permainan Berbasis Augmented Reality pada Perangkat Bergerak sebagai Media untuk Meningkatkan Kepedulian pada Hewan Langka - Fransnesa Fransnesa; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The population of orangutans from year to year has declined, the possibility of this population decline will continue to occur, one of the main reasons for the decline of the orangutan population due to the wild capture and trafficking by humans. Community awareness about the animal extinction problem, especially orangutans, can be said still low, therefore media needed to increase public awareness of it since early age. The most pleasurable and acceptable media of the community is through a game. This research will develop game that made to increase the awareness of animal extinction, the game is made by using augmented reality technology. Based on the test results of two media experts, this game can be said very good for use with the percentage of eligibility are 84% and 86%. Testing also has done to children aged 6-13 years with results that said game is fun and can increase care to orangutans. This is evidenced by the test results stating the percentage of the feasibility of the game is 81.39% or can be said very good.